2020
DOI: 10.14715/cmb/2020.66.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antimicrobial action and effect of active chitosan-gelatin biopolymeric films containing Thymus vulgaris, Ocimum basilicum and Origanum majorana essential oils against Escherichia coli and Staphylococcus aureus

Abstract: To replace synthetic preservatives and expand green consumption, several essential oils have been tested in foods and food packaging due to their antimicrobial properties. This study aimed to analyze the synergistic antimicrobial action of a chitosan-gelatin based active biopolymers with the addition of essential oils (EOs). The antimicrobial agents were tested against foodborne microorganisms Staphylococcus aureus and Escherichia coli strains. The antibacterial activity of Thymus vulgaris, Ocimum basilicum, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, different EOs having a synergistic antimicrobial activity can be combined and added to chitosan-based films to limit the organoleptic defects often reported following the addition of single EOs at concentrations needed to effectively inhibit microbial food spoilage. This strategy was successfully used for inhibiting E. coli and S. aureus growth [ 26 ]. These authors also reported that Origanum majorana and Ocimum basilicum EOs mixture had an additive effect against both E. coli and S. aureus and that adding a mixture of Origanum majorana and Thymus vulgaris EOs in chitosan-gelatin films was the only combination of EOs active against these two bacterial species.…”
Section: Components Of Edible Filmsmentioning
confidence: 99%
“…Moreover, different EOs having a synergistic antimicrobial activity can be combined and added to chitosan-based films to limit the organoleptic defects often reported following the addition of single EOs at concentrations needed to effectively inhibit microbial food spoilage. This strategy was successfully used for inhibiting E. coli and S. aureus growth [ 26 ]. These authors also reported that Origanum majorana and Ocimum basilicum EOs mixture had an additive effect against both E. coli and S. aureus and that adding a mixture of Origanum majorana and Thymus vulgaris EOs in chitosan-gelatin films was the only combination of EOs active against these two bacterial species.…”
Section: Components Of Edible Filmsmentioning
confidence: 99%
“…For the purposes of the food industry, OrO is often not added to the product itself, but is incorporated into biocomposite packaging films or other types of edible coatings. Edible coatings based on polysaccharides are environmentally friendly alternatives and can reduce the use of chemical preservatives [39][40][41][42][43][44]. The application of such packages is investigated for numerous types of raw or processed foods such as pork, ham, chicken wingettes, fish fillets, seafood, vegetables, fruits, juices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This would indicate that a formulation using MIC values would be sufficient for dermatological application in order to avoid hemolysis and prevent the entry of pathogens into open wounds . Likewise, this formulation can be a promising protective film for foods since other films previously reported in the literature presented values above those reported in this study. …”
Section: Resultsmentioning
confidence: 99%